PERAN KUA DALAM PENCEGAHAN PERNIKAHAN DINI BERDASARKAN UNDANG-UNDANG PERKAWINAN - Laura Abbas Jackson; Diding Rahmat (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN, 2025)
Early marriage is a serious problem that impacts the social, economic, and psychological aspects of children. The Indonesian government, through Law No. 16 of 2019, has revised the minimum age for marriage for women to 19 years, as a strategic effort to protect children's rights. This study aims to analyze the role of the Office of Religious Affairs (KUA) in preventing early marriage practices as mandated by the law. The research method used is a normative and empirical juridical approach, with data collection techniques through literature studies and interviews with KUA officers and the community. The results show that the KUA has an important role in the legal education process, administrative verification of the age of prospective brides and grooms, and providing recommendations for marriage dispensations. However, structural obstacles are still found such as weak coordination between institutions and limited public access to information on new regulations. Therefore, strengthening the institutional capacity of the KUA and integrating legal education programs comprehensively need to be optimized to achieve maximum legal protection for children.